A green and sustainable approach for the synthesis of 1, 5-benzodiazepines and spirooxindoles in one-pot using a MIL-101(Cr) metal–organic framework as a reusable catalyst. (8th October 2021) - Sarkar, Fillip Kumar; Gupta, Ajay; Jamatia, Ramen; Anal, Jasha Momo H.; Pal, Amarta Kumar
Abstract : Green and efficient protocols for the synthesis of 1, 5-benzodiazepines and spirooxindoles were developed utilizing MIL-101(Cr) in SFRC and water as solvent respectively. Abstract : Metal–organic framework MIL-101(Cr) has been efficiently utilized for the synthesis of biologically relevant heterocycles such as 1, 5-benzodiazepines and spirooxindoles in one-pot. MIL-101(Cr) was prepared via a solvothermal method and characterized by FT-IR, PXRD, SEM, TEM, EDX, and ICP-OES analysis. Thermogravimetric analysis (TGA) described its high thermal stability. Low catalyst loading, easy separation, reusability, and high yields are some salient features of the protocols. Solvent-free reaction conditions (SFRC) or water as solvent are some additional benefits in the field of green and sustainable process development.